Fiscal and non-fiscal institutional context effects and foreign direct investment: Empirical evidence in developing countries - Dimitra Mitsi; Constantina Kottaridi (SPOUDAI - Journal of Economics and Business, 2022)
In this paper, we examine the impact of different types of institutions including fiscal rules to the conventional institutional framework on FDI in 24 developing countries from 1996 to 2018. No study to date explores the role of fiscal rules on FDI given that fiscal discipline came to the forefront after the 2008 financial crisis. Our findings support a significant negative effect of expenditure rules on FDI, indicating that such fiscal rules act as a signal of fiscal indiscipline. We also provide strong evidence that political stability, regulatory quality and rule of law have a positive effect on FDI. Interestingly, we find an asymmetric impact of political stability and regulatory quality on FDI when we adopt expenditure rules in developing countries in contrast to those not adopting expenditure rules.
Keywords: C33; E62; F21; 330; Fiscal policy; fiscal rules; foreign direct investment; institutional context